Moringa Leaves (Moringa Oleifera) Improve Reproductive Health in Women of Childbearing Age: Literature Review - Widiastini, Luh Putu; Karuniadi, I Gusti Agung Manik (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Nutritional status is significantly related to reproductive health. The impact of undernutrition on women of childbearing age includes menstrual disorders, anemia, infertility, pregnancy disorders, fetal and decreased milk production during breastfeeding. The utilization of natural materials can be developed in improving nutritional status, so as to improve reproductive health, one of which is Moringa leaves. Moringa is a useful plant that is widely used as a medicinal plant and food so it is called the Amazing Tree and The Miracle Tree. The purpose of this literature study, to determine the utilization of Moringa leaves on the reproductive health of women of childbearing age. This literature study utilizes databases from google scholar, pubmed, science direct with the keywords moringa oleifera, reproductive health, women. The number of articles obtained was 11 articles that fit the criteria. The articles used are in English and Indonesian with the limitation of the year published above 2019. Conclusion; The high content of nutrients makes Moringa has functional properties for health and overcomes nutritional deficiencies in women of childbearing age such as maintaining the balance of reproductive hormones, increasing hemoglobin levels in reducing the incidence of anemia and increasing breast milk production.